2007
DOI: 10.1007/s11693-007-9006-8
|View full text |Cite
|
Sign up to set email alerts
|

Designing sequential transcription logic: a simple genetic circuit for conditional memory

Abstract: The ability to learn and respond to recurrent events depends on the capacity to remember transient biological signals received in the past. Moreover, it may be desirable to remember or ignore these transient signals conditioned upon other signals that are active at specific points in time or in unique environments. Here, we propose a simple genetic circuit in bacteria that is capable of conditionally memorizing a signal in the form of a transcription factor concentration. The circuit behaves similarly to a ''d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
0
30
0
1
Order By: Relevance
“…A previous theoretical analysis [24] has shown that simple combinations of protein-DNA and protein-protein interactions suffice to turn a genetic toggle switch into a conditional memory unit, which memorizes a signal only when given a read “command”, akin to a Data latch in digital electronics. Here, we explore whether the same set of interactions also enable the design of a toggle command, which is intrinsically more complex, since it makes the output dependent on the memorized signal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous theoretical analysis [24] has shown that simple combinations of protein-DNA and protein-protein interactions suffice to turn a genetic toggle switch into a conditional memory unit, which memorizes a signal only when given a read “command”, akin to a Data latch in digital electronics. Here, we explore whether the same set of interactions also enable the design of a toggle command, which is intrinsically more complex, since it makes the output dependent on the memorized signal.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, for the core memory unit of Fig. 1A, we chose a ‘genetic toggle switch’ consisting of two mutually repressing genes, the implementation of which was one of the first milestones in synthetic biology [22] and served as the basis for simple sequential logics [23], [24]. Genetic switches of this kind have later also been identified as important elements of the Drosophila gap gene network [25].…”
Section: Introductionmentioning
confidence: 99%
“…The standard part libraries and toolboxes of well-characterized genetic components have been constructed through numerous laboratory experiments over the last decade [10][11][12][13][14][15][16][17][18]. These components have been extensively used to develop genetic circuits with different functionalities including oscillators [3], amplifiers [19,20], linearizer gene circuit [21], memory devices [22,23], switches [1,12,24], time-delay circuits [25,26], genetic logic gates [27][28][29][30] etc. …”
Section: Introductionmentioning
confidence: 99%
“…The capacity of GRNs to learn associations in shorter, non-evolutionary time-scales has also been studied theoretically using GRN models. Learning in these models is restricted to a small subset of predefined stimuli [18], [19], [20], [21] and thus the computational capabilities of these GRN models are limited compared to neural network models.…”
Section: Introductionmentioning
confidence: 99%